A Fast and Responsive Turn-On Fluorescent Probe Based on a Quinone Conjugated Alkoxy Derivative for Biothiols and a Cellular Imaging Study - Nemetova, Ulviyye; Onem, Ayse Nur; Er, Alev; Celik, Sefa; Ozel, Aysen E.; AKYÜZ, SEVİM; Ozyurek, Mustafa; Ayla, Sibel Sahinler (Tubitak Scientific & Technological Research Council Turkey, 2024)
The detection of intracellular biothiols (cysteine, N-acetyl cysteine, and glutathione) with high selectivity and sensitivity is important to reveal biological functions. In this study, a 2-(2-methoxy-4-methylphenoxy)-3-chloro-5,8-dihydroxynaphthalene-1,4dione (DDN-O) compound (3) was newly synthesized and used as a fluorogenic probe (detector molecule) in the fluorometric method for the rapid, highly selective, and sensitive determination of biothiols. The intensity values (lambda ex = 260 nm, lambda em = 620 nm) of the product were measured by adding biothiols to the reaction medium at varying concentrations and the glutathione equivalent thiol content values of each biothiol were calculated. Using compound 3, glutathione as the reference biothiol was detected in the linear concentration range of 10-70 mu M and the LOD value was found to be 0.11 mu M. Biothiol detection with structurally simple compound 3 was performed at the cellular level within 1 min and the probe was also successfully used in bioimaging with low cytotoxicity. It was concluded that this probe can serve as an alternative to existing fluorescence-based biothiol probes with applications in rapid biothiol detection at the cellular level for biological functions. To evaluate the molecular structure of 3, conformational analysis was performed using the PM3 semiempirical method. The most stable obtained molecular geometry was then optimized at the DFT/wb97xd/6-311++G(d,p) level of theory. Frontier molecular orbitals (HOMO and LUMO) and molecular electrostatic potential map analyses were performed for the optimized structure. Molecular docking studies demonstrated the interactions of 3 with HAS (1AO6) and FhGST (2FHE) target proteins.
Keywords: Biothiols; Fluorogenic Probe; Bioimaging; Molecular Modeling; Molecular Docking